Clinical significance of circulating tumor DNA monitoring based on TP53 mutation in high-grade serous ovarian cancer patients - Jung, Heejung; Kang, Ok-Ju; Lee, Young-Jae; Kang, Sung Wan; Lee, Min-Seo; Lee, Shin-Wha; Kim, Yong Man (Translational Cancer Research; Vol 15, No 4 (April 30, 2026): Translational Cancer Research, 2026)
High-grade serous ovarian cancer (HGSOC) is characterized by aggressive clinical behavior and a high risk of recurrence. Cancer antigen 125 (CA-125) is widely used for monitoring treatment response and disease recurrence; however, its limited sensitivity and specificity, particularly during surveillance, highlight the need for more reliable biomarkers. Circulating tumor DNA (ctDNA) has emerged as a promising tool for real-time disease monitoring, and TP53 mutations—present in nearly all HGSOC cases—provide an ideal target for personalized ctDNA-based assays. This study evaluated the translational utility of patient-specific TP53 mutation-based ctDNA monitoring using droplet digital PCR (ddPCR) in patients with HGSOC.